2018
DOI: 10.3892/mmr.2018.9086
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic acid B reverses multidrug resistance in nude mice bearing human colon cancer stem cells

Abstract: Salvianolic acid B (SalB) is a water-soluble phenolic compound, extractable from Salvia miltiorrhiza, and has previously been demonstrated to reverse tumor multidrug resistance (MDR) in colon cancer cells. Cancer stem cells (CSCs) are closely associated with drug resistance. Therefore, establishing a nude mouse model bearing human colon CSCs is important for the study of the mechanisms underlying colon cancer drug resistance as well as the reversal of drug resistance. The present study aimed to establish a nud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 37 publications
(34 reference statements)
0
20
0
1
Order By: Relevance
“…no. C0105; Beyotime Institute of Biotechnology) as previously described (26), and examined using a light microscope (BX51; Olympus Corporation; magnification, ×400). The nuclear was stained blue and cytoplasm was stained red.…”
Section: Methodsmentioning
confidence: 99%
“…no. C0105; Beyotime Institute of Biotechnology) as previously described (26), and examined using a light microscope (BX51; Olympus Corporation; magnification, ×400). The nuclear was stained blue and cytoplasm was stained red.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Danshensu, an active component of salvianolic acids, inhibited the development of melanoma by affecting tumor angiogenesis and tumor invasion (Zhang et al, 2010). Guo et al (2018) demonstrated that Sal B reversed tumor MDR by down-regulating the expression of CD44, SOX2 and ABCG2 proteins in LoVo and HCT-116 colonic CSC xenografts. A recent study by Wu et al (2018) indicated that S. miltiorrhiza extract inhibited hepatocarcinogenesis by modulating TGF-β/TβR and Imp7/8 protein expression, suggesting that S. miltiorrhiza has multiple targets in HCC treatment.…”
Section: Potential Applications Of Salvianolic Acids For the Treatmenmentioning
confidence: 99%
“…在 乳腺癌中, 丹酚酸A能够下调transgelin 2的表达, 逆转 乳腺癌对紫杉醇的耐药 [99,100] . 在结肠癌中, 丹酚酸B能 够抑制肿瘤干细胞的活性, 逆转结肠癌的多药耐药 [101] . 藤黄酸(gambogic acid)是中药藤黄的主要活性成 分.…”
Section: 姜黄素(Curcumin)是来源于传统中药姜黄的有效unclassified